Preliminary phytochemical screening and Evaluation of hepatoprotective activity of ethanolic extract of whole plant of Evolvulus alsinoides using CCl4 induced model in experimental animals - Gomathi Periasamy; Syeda Hafsa Mehjabeen; Krishna Prasad; Syeda Husna Fatima; Shalini Thakkallapelly (International Journal of Phytomedicine, 2018)
Present study was conducted to evaluate the preliminary phytochemical screening and hepatoprotective activity of whole plant of Evolvulus alsinoides. The whole plant was defatted with petroleum ether and then extracted with 90 % ethanol. The phytochemical screening was done for ethanol extract using standard procedures. Acute toxicity was done using OECD 423 guidelines and the extract was found to be practically non-toxic upto a dose of 1500mg/kg b.w. when given orally. Hepatoprotective activity was evaluated using Carbon tetra chloride induced model in rats. In CCl4 induced mothod of 90% Ethanolic extract of whole plant of Evolvulus alsinoides (75 & 150mg/kg b.w.) produced significant dose dependent hepatoprotective activity. Histopathological studies could be carried out to assess the degree of damage. The hepatoprotective effect of the aforesaid extract was substantiated by pentobarbital sleeping time experiment in mice. The effect of the extracts at 150 mg/kg was compared to that of the reference drug, Silymarin (50 mg/kg). In vitro antioxidant studies were conducted to confirm the antioxidant mechanism involved in their hepatoprotective activity in CCl4-induced in rats. The presence of flavonoids could be responsible for hepatoprotective activity.